Application of MAT Methodology in the Evaluation of Prescribing Adherence to Clinical Practice Guidelines for Secondary Prevention of Coronary Heart Disease in Post-Acute Coronary Syndrome Patients in Kuwait - Al-Taweel, Dalal; Awad, Abdelmoneim (Frontiers in Pharmacology, 2021)
Quantification of prescribers’ adherence to evidence-based guidelines can be used as an outcome measure to assess the impact of services on the quality of medication use. Additionally, it can help in reducing inappropriate interventions and ensure that high-quality care is provided to patients. This study aimed to evaluate prescribing practices for secondary prevention of coronary heart disease (CHD) in post-acute coronary syndromes (ST-Elevation Myocardial Infarction [STEMI] or non-ST elevation acute coronary syndrome [NSTEACS] patients using two medication assessment tools (MATs) at secondary and tertiary healthcare settings in Kuwait. Both MATs were developed and validated based on the relevant guidelines issued by the European Society of Cardiology and the American College of Cardiology/American Heart Association. A quantitative cross-sectional multi-center study was conducted on 460 patients’ medical records collected randomly from six healthcare facilities in Kuwait. Application of MATSTEMI on 232 patients’ medication records (with 85.9% applicability) resulted in intermediate overall adherence (69.8%; 95% CI: 67.6-72.0). Application of MATNSTEACS on 228 patients’ medication records (with applicability 83.2%) resulted in intermediate overall adherence (73.3%; 95% CI: 70.5-76.0). There was no significant difference between the percentages of overall adherence among patients managed post-NSTEACS compared to those managed post-STEMI (p=0.05). Multivariable logistic regression analysis revealed that the overall adherence to the MATSTEMI criteria was significantly higher among the specialized cardiac centers compared to the general hospitals (OR: 1.6; 95% CI: 1.1-2.3; p=0.02). The overall adherence to the MATNSTEACS criteria was found to be significantly lower among non-Kuwaitis compared to Kuwaitis (OR: 0.6; 95% CI: 0.5-0.9; p=0.01) and patients with serum LDL 1.8 mmol/L compared to those with serum LDL-C < 1.8 mmol/L (OR: 0.5; 95% CI: 0.4-0.7; p<0.001). The present findings revealed that both MATs were useful tools in identifying the standard of clinical performances as well as highlighting areas for improvement regarding secondary prevention of CHD in post-acute coronary syndromes patients.